A blacksmithing primer : a course in basic and intermediate blacksmithing - McDaniel, Randy (Minneapolis, MN : Hobar, 2004)
Details forging techniques from the start to finish, beginning with the building of your own forge to making tools and elaborate door knockers.
Includes index.
Also issued online.
Keywords: Blacksmithing -- Amateurs' manuals